Hubungan penampilan induk anak domba dari berbagai tipe kelahiran (Faculty of Animal Science, Universitas Brawijaya, 2010)
The objectives of the study was to analyse the relationship between dam and their offspring on the basis of body measurement and body weight at some partus types. In this study, 85 ewes and 127 lamb were used as materials. Purposive sampling was used to determine the samples of partum type of ewes having single (A1), twin (A2) and more than two lambs (AL2). Parameters measured were the body length, shoulder height, hip width, chest circumference and chest width. The results showed that all body measurement of dam related to the lambs. The highest correlation were in ≥ P2 for shoulder height, chest circumference, hip width and body length. Those were 0.310: 0.702: - 0.655 and 0.373 respectively. In conclusion, there was relationship on all birth type and parameters between dam and lambs. The AL2 showed closer relationship as compared to that of A1 and A2. Those were body length, shoulder height, chest circumference and hip width. Keywords: body measurements, regression, birth type, sheep